Surface treatment method for selective laser melting titanium alloy sample piece

Through a multi-step surface treatment method including sandblasting, polishing, acid immersion and ultrasonic cleaning, the problem of fluorescence penetration inspection and roughness of complex samples in the aerospace field is solved, and efficient and economical surface treatment is achieved Effect.

CN119426622APending Publication Date: 2025-02-14飞而康快速制造科技有限责任公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411539725.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to meet the fluorescence penetration inspection and roughness requirements of complex samples in the aerospace field, and polishing treatment is prone to dimensional deviations and surface damage.

Method used

A surface treatment method including a first sandblasting treatment, a polishing treatment, a second sandblasting treatment, an acid liquid soaking, an ultrasonic cleaning and a purge treatment are adopted. The method further improves the surface quality by sandblasting, polishing and smoothing the surface, acid liquid and ultrasonic cleaning.

Benefits of technology

The efficient surface treatment of selected laser-melted titanium alloy samples is achieved, so that they can meet the requirements of fluorescence permeation inspection and roughness, while reducing the cost of multiple detections.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119426622A_ABST
    Figure CN119426622A_ABST
Patent Text Reader

Abstract

The invention provides a surface treatment method for a selective laser melting titanium alloy sample piece. The surface treatment method comprises the following steps that the titanium alloy sample piece to be treated is sequentially subjected to first sand blasting treatment, polishing treatment, second sand blasting treatment, acid liquor immersion cleaning, ultrasonic cleaning and purging treatment. By adopting the surface treatment method provided by the invention, the selective laser melting titanium alloy sample can be efficiently and quickly treated, so that the selective laser melting titanium alloy sample can smoothly pass a fluorescent penetration test at one time while the surface roughness and the dimensional deviation are within a required range, and the cost caused by multiple fluorescent penetration tests is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material surface treatment, and in particular relates to a surface treatment method for a selective laser melting titanium alloy sample. Background Art

[0002] Selective Laser Melting (SLM) is an advanced metal additive manufacturing technology that selectively melts metal powder layers with a high-energy-density laser beam to build three-dimensional solid parts layer by layer. The advantage of SLM technology is that it can produce complex metal components with high degrees of freedom and generate nearly 100% high-density parts, which can be widely used in aerospace, medicine, automobile and other fields.

[0003] In the field of aerospace, there are some complex samples (such as a ring with many thin blades), which usually need to be obtained by selective laser melting technology. However, in the contour scanning of the laser selective melting forming process, since the laser energy is Gaussian distributed, the energy density at the edge of the laser is low, and the powder cannot be completely melted, so that some semi-melted powder will adhere to the surface of the formed part. However, complex samples in the field of aerospace usually have surface quality requirements, mainly through fluorescent penetrant inspection and achieving roughness. Therefore, complex samples will be polished.

[0004] At present, the polishing process of complex samples in the aerospace field is difficult to meet the requirements of fluorescent penetrant inspection and roughness. The reasons are: (1) The workpiece needs to be inspected for fluorescence, but the local position of the workpiece is too small and there is no polishing head of suitable size, so the local position cannot be reached. During the inspection, it is found that the local position is densely dotted; (2) Polishing can easily cause dimensional deviation; (3) The polishing head is made of hard metal, and long-term polishing can easily cause surface damage, which can easily cause accumulation of fluorescent liquid in the damaged defects, so the fluorescent penetrant inspection cannot pass.

[0005] In summary, for the selective laser melted alloy samples, it is necessary to provide a surface treatment method that can meet the roughness requirements and pass the fluorescent penetrant inspection. Summary of the invention

[0006] The purpose of the present invention is to provide a surface treatment method for selective laser melting titanium alloy samples. The surface treatment method can simply and efficiently realize the treatment of selective laser melting titanium alloy samples, so that the surface roughness and dimensional deviation are within the required range, and the fluorescent penetrant test can be successfully passed in one time, thereby reducing the cost caused by multiple fluorescent penetrant tests.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] The present invention provides a surface treatment method for a selective laser melting titanium alloy sample, the surface treatment method comprising the following steps:

[0009] The titanium alloy sample to be processed is subjected to a first sandblasting treatment, a polishing treatment, a second sandblasting treatment, an acid solution immersion treatment, an ultrasonic cleaning treatment and a purging treatment in sequence.

[0010] The surface treatment method provided by the present invention has a simple process flow and is easy to operate. It can meet the roughness requirements and pass the fluorescent penetration test at one time. The dimensional deviation of the titanium alloy sample before and after the treatment is within the requirements.

[0011] As a preferred technical solution of the present invention, the thickness of the selective laser melted titanium alloy sample is ≤1.2mm, for example, it can be 1.2mm, 1.1mm, 1.0mm, 0.9mm, 0.8mm, 0.7mm or 0.6mm, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0012] As a preferred technical solution of the present invention, the pressure of the first sandblasting treatment is 0.5-0.55 MPa, for example, it can be 0.5 MPa, 0.51 MPa, 0.52 MPa, 0.53 MPa, 0.54 MPa or 0.5 MPa, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0013] Preferably, the single-point residence time of the first sandblasting treatment is 10 to 15 s, for example, 10 s, 11 s, 12 s, 13 s, 14 s or 15 s, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0014] Preferably, the blasting medium used in the first blasting process comprises black corundum.

[0015] Preferably, the average particle size of the black corundum is 80-100 mesh, for example, 80 mesh, 84 mesh, 88 mesh, 92 mesh, 96 mesh or 100 mesh, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0016] In the present invention, the purpose of the first sandblasting treatment is to remove impurities on the surface of the titanium alloy sample to be treated.

[0017] As a preferred technical solution of the present invention, the polishing process includes polishing with a polishing head and ultrasonic polishing performed sequentially.

[0018] As a preferred technical solution of the present invention, the polishing head used for polishing comprises a resin polishing head.

[0019] Preferably, the precision of the resin polishing grinding head is 150-320 mesh, for example, it can be 150 mesh, 170 mesh, 190 mesh, 210 mesh, 230 mesh, 250 mesh, 270 mesh, 290 mesh or 320 mesh, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0020] Preferably, the polishing time of the polishing head is 6 to 15 minutes, for example, it can be 6 minutes, 7 minutes, 8 minutes, 9 minutes, 10 minutes, 11 minutes, 12 minutes, 13 minutes, 14 minutes or 15 minutes, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0021] It is worth noting that the polishing end point of the polishing head is: no printed lines can be seen.

[0022] As a preferred technical solution of the present invention, the polishing medium used in the ultrasonic polishing includes fiber oilstone.

[0023] Preferably, the particle size of the fiber oilstone is 120-180#, for example, it can be 120#, 130#, 140#, 150#, 160#, 170# or 180#, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0024] Preferably, the ultrasonic polishing time is 3 to 8 minutes, for example, 3 minutes, 4 minutes, 5 minutes, 6 minutes, 7 minutes or 8 minutes, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0025] It is worth noting that the polishing head polishing described in the present invention is used for polishing the planar structure, and the ultrasonic polishing is used to process the R corner of the workpiece and the parts that are not easy to be polished by the polishing head; performing polishing with the polishing head and ultrasonic polishing in sequence can achieve all-round polishing of the sample to be processed to avoid omissions.

[0026] In addition, the particle size of the fiber oilstone used in the ultrasonic polishing process is 120-180#. If the particle size is too large, it will lead to a large amount of workpiece size removal in the same time. If the particle size is too small, it will lead to a longer working time for the same amount of workpiece size removal.

[0027] As a preferred technical solution of the present invention, the pressure of the second sandblasting treatment is 0.5-0.55 MPa, for example, it can be 0.5 MPa, 0.51 MPa, 0.52 MPa, 0.53 MPa, 0.54 MPa or 0.44 MPa, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0028] Preferably, the single-point residence time of the second sandblasting treatment is 7 to 12 s, for example, 7 s, 8 s, 9 s, 10 s, 11 s or 12 s, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0029] Preferably, the blasting medium used in the second blasting process comprises black corundum.

[0030] Preferably, the average particle size of the black corundum is 80-100 mesh, for example, 80 mesh, 84 mesh, 88 mesh, 92 mesh, 96 mesh or 100 mesh, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] In the present invention, the second sandblasting process is used to remove scratches and impurities such as floating and sinking caused by the polishing process.

[0032] As a preferred technical solution of the present invention, the mixed acid used for the acid leaching includes nitric acid, hydrofluoric acid and water.

[0033] Preferably, the mass ratio of nitric acid, hydrofluoric acid and water is 3-4:1-2:5, for example, it can be 3:1:5, 3:2:5, 3:1.5:5, 3.5:1:5, 3.5:1.5:5, 3.5:2:5, 4:1:5, 4:1.5:5 or 4:2:5, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0034] Preferably, the concentration of the nitric acid is 65-68wt%, for example, it can be 65wt%, 65.5wt%, 66wt%, 66.5wt%, 67wt%, 67.8wt% or 68wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] Preferably, the concentration of the hydrofluoric acid is ≥40wt%, for example, it can be 40wt%, 41wt%, 42wt%, 43wt%, 44wt% or 45wt%, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0036] Preferably, the acid solution immersion time is 3 to 15 minutes, for example, 3 minutes, 5 minutes, 7 minutes, 9 minutes, 11 minutes, 13 minutes or 15 minutes, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] It is worth noting that the acid immersion time of the present invention is 3 to 15 minutes. If the time is too short, the roughness of the workpiece surface cannot meet the requirements. If the time is too long, the workpiece surface will be corroded too much, large-area pits will appear, and the workpiece size will become smaller.

[0038] As a preferred technical solution of the present invention, the temperature of the ultrasonic cleaning is 40-50°C, for example, it can be 40°C, 42°C, 44°C, 46°C, 48°C or 50°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0039] Preferably, the ultrasonic cleaning time is 30 to 40 minutes, for example, 30 minutes, 32 minutes, 34 minutes, 36 minutes, 38 minutes or 40 minutes, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0040] Preferably, the cleaning liquid used for the ultrasonic cleaning includes a hydrocarbon cleaning agent.

[0041] It is worth noting that the hydrocarbon cleaning agent of the present invention contains water, and the amount of water used is related to the volume of the device used in the ultrasonic cleaning process.

[0042] As a preferred technical solution of the present invention, the surface treatment method of a titanium alloy sample by selective laser melting provided by the present invention comprises the following steps:

[0043] The titanium alloy sample to be processed with a thickness of ≤1.2 mm is sequentially subjected to the first sandblasting treatment, polishing treatment, the second sandblasting treatment, acid immersion, ultrasonic cleaning and purging treatment;

[0044] The pressure of the first sandblasting treatment is 0.5-0.55 MPa, the single point residence time is 10-15 s, and the sandblasting medium used includes black corundum with an average particle size of 80-100 mesh;

[0045] The polishing process includes polishing with a polishing head and ultrasonic polishing performed in sequence; the polishing time of the polishing head is 6 to 15 minutes, and the polishing head used includes a resin polishing head with a precision of 150 to 320 meshes; the ultrasonic polishing time is 3 to 8 minutes, and the polishing medium used includes a fiber oilstone with a particle size of 120 to 180#;

[0046] The pressure of the second sandblasting treatment is 0.5-0.55 MPa, the single point residence time is 7-12 s, and the sandblasting medium used includes black corundum with an average particle size of 80-100 mesh;

[0047] The acid leaching time is 3 to 15 minutes, and the mixed acid used includes nitric acid, hydrofluoric acid and water in a mass ratio of 3 to 4:1 to 2:5; the concentration of the nitric acid is 65 to 68 wt%, and the concentration of the hydrofluoric acid is ≥ 40 wt%;

[0048] The temperature of the ultrasonic cleaning is 40-50° C., the time is 30-40 minutes, and the cleaning liquid used includes a hydrocarbon cleaning agent.

[0049] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0050] Compared with the prior art, the present invention has the following beneficial effects:

[0051] (1) The selected laser melted titanium alloy sample treated by the surface treatment method provided by the present invention can successfully pass the fluorescent penetrant test at one time, reducing the cost caused by multiple fluorescent penetrant tests;

[0052] (2) The surface treatment method provided by the present invention can greatly reduce the time required for post-processing of the selected laser melted titanium alloy sample after printing, and provide a treatment idea for post-processing of other samples;

[0053] (3) The surface treatment method provided by the present invention has a simple process flow and can meet the requirements for the roughness of the workpiece. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 This is a graph showing the results of the fluorescent penetration test of the selected laser melted titanium alloy sample after treatment provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0055] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0056] Example 1

[0057] This embodiment provides a surface treatment method for a titanium alloy sample by selective laser melting, the surface treatment method comprising the following steps:

[0058] The titanium alloy sample to be processed with a thickness of 1.0 mm is sequentially subjected to a first sandblasting treatment, a polishing treatment, a second sandblasting treatment, an acid solution immersion treatment, an ultrasonic cleaning treatment, and a purging treatment;

[0059] The pressure of the first sandblasting treatment is 0.55 MPa, the single point residence time is 10 s, and the sandblasting medium used includes black corundum with an average particle size of 80 mesh;

[0060] The polishing process includes polishing with a polishing head and ultrasonic polishing performed in sequence; the polishing time of the polishing head is 10 minutes, and the polishing head used is a resin polishing head with a precision of 320 meshes; the ultrasonic polishing time is 3 minutes, and the polishing medium used includes a fiber oilstone with a particle size of 180#;

[0061] The second sandblasting treatment has a pressure of 0.55 MPa, a single point residence time of 7 s, and the sandblasting medium used includes black corundum with an average particle size of 80 mesh;

[0062] The acid leaching time is 15 minutes, and the mixed acid used includes nitric acid, hydrofluoric acid and water in a mass ratio of 4:1:5; the concentration of the nitric acid is 68wt%, and the concentration of the hydrofluoric acid is 40wt%;

[0063] The temperature of the ultrasonic cleaning is 45° C., the time is 35 min, and the cleaning liquid used is a hydrocarbon cleaning agent.

[0064] The sample treated in this embodiment is subjected to fluorescence detection, and the results are as follows: Figure 1 shown.

[0065] Example 2

[0066] This embodiment provides a surface treatment method for a titanium alloy sample by selective laser melting, the surface treatment method comprising the following steps:

[0067] The titanium alloy sample to be processed with a thickness of 1.2 mm is sequentially subjected to a first sandblasting treatment, a polishing treatment, a second sandblasting treatment, an acid solution immersion treatment, an ultrasonic cleaning treatment, and a purging treatment;

[0068] The pressure of the first sandblasting treatment is 0.5 MPa, the single point residence time is 15 s, and the sandblasting medium used includes black corundum with an average particle size of 100 mesh;

[0069] The polishing process includes polishing with a polishing head and ultrasonic polishing performed in sequence; the polishing time of the polishing head is 15 minutes, and the polishing head used includes a resin polishing head with a precision of 150 mesh; the ultrasonic polishing time is 8 minutes, and the polishing medium used includes a fiber oilstone with a particle size of 120#;

[0070] The second sandblasting treatment has a pressure of 0.5 MPa, a single-point residence time of 12 s, and the sandblasting medium used includes black corundum with an average particle size of 100 mesh;

[0071] The acid leaching time is 3 minutes, and the mixed acid used includes nitric acid, hydrofluoric acid and water in a mass ratio of 4:2:5; the concentration of the nitric acid is 65wt%, and the concentration of the hydrofluoric acid is 45wt%;

[0072] The temperature of the ultrasonic cleaning is 40° C., the time is 40 min, and the cleaning liquid used is a hydrocarbon cleaning agent.

[0073] Example 3

[0074] This embodiment provides a surface treatment method for a titanium alloy sample by selective laser melting, the surface treatment method comprising the following steps:

[0075] The titanium alloy sample to be processed with a thickness of 1.0 mm is sequentially subjected to a first sandblasting treatment, a polishing treatment, a second sandblasting treatment, an acid solution immersion treatment, an ultrasonic cleaning treatment, and a purging treatment;

[0076] The pressure of the first sandblasting treatment is 0.52 MPa, the single point residence time is 12 s, and the sandblasting medium used includes black corundum with an average particle size of 90 mesh;

[0077] The polishing process includes polishing with a polishing head and ultrasonic polishing performed in sequence; the polishing time of the polishing head is 9 minutes, and the polishing head used includes a resin polishing head with a precision of 230 meshes; the ultrasonic polishing time is 6 minutes, and the polishing medium used includes a fiber oilstone with a particle size of 150#;

[0078] The second sandblasting treatment has a pressure of 0.52 MPa, a single point residence time of 10 s, and the sandblasting medium used includes black corundum with an average particle size of 90 mesh;

[0079] The acid leaching time is 8 minutes, and the mixed acid used includes nitric acid, hydrofluoric acid and water in a mass ratio of 3:1:5; the concentration of the nitric acid is 66wt%, and the concentration of the hydrofluoric acid is 42wt%;

[0080] The temperature of the ultrasonic cleaning is 50° C., the time is 30 minutes, and the cleaning liquid used is a hydrocarbon cleaning agent.

[0081] Example 4

[0082] This embodiment provides a surface treatment method for a selective laser melted titanium alloy sample. The surface treatment method is different from that of Embodiment 1 only in that:

[0083] In this embodiment, the pressure of the first sandblasting process is adjusted to 0.45 MPa.

[0084] Example 5

[0085] This embodiment provides a surface treatment method for a selective laser melted titanium alloy sample. The surface treatment method is different from that of Embodiment 1 only in that:

[0086] In this embodiment, the pressure of the first sandblasting process is adjusted to 0.6 MPa.

[0087] Example 6

[0088] This embodiment provides a surface treatment method for a selective laser melted titanium alloy sample. The surface treatment method is different from that of Embodiment 1 only in that:

[0089] In this embodiment, the polishing process of the polishing grinding head is omitted.

[0090] Example 7

[0091] This embodiment provides a surface treatment method for a selective laser melted titanium alloy sample. The surface treatment method is different from that of Embodiment 1 only in that:

[0092] This embodiment omits the ultrasonic polishing process.

[0093] Example 8

[0094] This embodiment provides a surface treatment method for a selective laser melted titanium alloy sample. The surface treatment method is different from that of Embodiment 1 only in that:

[0095] In this embodiment, the mass ratio of nitric acid, hydrofluoric acid and water in the acid solution leaching process is adjusted to 5:2:5.

[0096] Example 9

[0097] This embodiment provides a surface treatment method for a selective laser melted titanium alloy sample. The surface treatment method is different from that of Embodiment 1 only in that:

[0098] In this embodiment, the mass ratio of nitric acid, hydrofluoric acid and water in the acid solution leaching process is adjusted to 3.5:4:5.

[0099] Example 10

[0100] This embodiment provides a surface treatment method for a selective laser melted titanium alloy sample. The surface treatment method is different from that of Embodiment 1 only in that:

[0101] In this embodiment, the temperature of the ultrasonic cleaning is adjusted to 25°C.

[0102] Embodiment 11

[0103] This embodiment provides a surface treatment method for a selective laser melted titanium alloy sample. The surface treatment method is different from that of Embodiment 1 only in that:

[0104] In this embodiment, the temperature of the ultrasonic cleaning is adjusted to 60°C.

[0105] Example 12

[0106] This embodiment provides a surface treatment method for a selective laser melted titanium alloy sample. The surface treatment method is different from that of Embodiment 1 only in that:

[0107] In this embodiment, the cleaning liquid used in the ultrasonic cleaning is adjusted to deionized water.

[0108] Comparative Example 1

[0109] This comparative example provides a surface treatment method for a selective laser-melted titanium alloy sample, and the surface treatment method is different from that of Example 1 only in that:

[0110] In this comparative example, the first sandblasting process was omitted.

[0111] Comparative Example 2

[0112] This comparative example provides a surface treatment method for a selective laser-melted titanium alloy sample, and the surface treatment method is different from that of Example 1 only in that:

[0113] In this comparative example, the second sandblasting process was omitted.

[0114] Comparative Example 3

[0115] This comparative example provides a surface treatment method for a selective laser-melted titanium alloy sample, and the surface treatment method is different from that of Example 1 only in that:

[0116] In this comparative example, the acid solution leaching is adjusted to alkaline solution leaching, wherein the alkaline solution used in the alkaline solution leaching is a sodium hydroxide solution with a concentration of 25wt%.

[0117] Performance testing:

[0118] The surface roughness test and size removal amount test were performed on the selected area laser melted titanium alloy samples obtained by the surface treatment methods provided in the above embodiments and comparative examples, and the results are shown in Table 1;

[0119] It is worth noting that when the size removal amount is ≤0.35mm, it can meet market demand.

[0120] Table 1

[0121]

[0122]

[0123] According to Table 1, we can know the following points:

[0124] (1) Comprehensive analysis of Examples 1-3 shows that the surface treatment method provided by the present invention can efficiently and quickly treat the selected laser melted titanium alloy sample, so that the surface roughness and dimensional deviation are within the required range, and the fluorescent penetrant test can be successfully passed at one time, reducing the cost caused by multiple fluorescent penetrant tests;

[0125] (2) Comprehensive analysis of Example 1 and Examples 4-5 shows that the pressure of the first sandblasting treatment affects the sandblasting effect. When the sandblasting pressure is too high, the sample will be severely worn, which will lead to a large dimensional deviation before and after the treatment, which cannot meet market demand; when the sandblasting pressure is too low, the sample will have a high roughness.

[0126] (3) Comprehensive analysis of Examples 6-7 shows that only by combining polishing with a polishing head and ultrasonic polishing can the sample be polished in all directions. Omitting any one of them will affect the surface treatment effect.

[0127] When polishing with a polishing head or ultrasonic polishing is omitted, the roughness of the sample will become higher;

[0128] (4) Comprehensive analysis of Example 1 and Examples 8-9 shows that the selection of mixed acid during acid leaching will affect the cleaning effect. When the nitric acid content in the mixed acid is too high, the sample size will be excessively lost, resulting in a large size deviation before and after treatment, which cannot meet market demand; when the hydrofluoric acid content is too high, the sample will be rapidly corroded and the size will shrink sharply, which cannot meet market demand;

[0129] (5) Comprehensive analysis of Example 1 and Examples 10-12 shows that, although the selection of process parameters during the ultrasonic cleaning process has little effect on the roughness and dimensional change of the sample, it will affect the appearance of the sample;

[0130] When the temperature of the ultrasonic cleaning is too high, the surface of the workpiece will be oxidized and yellowed; when the temperature is too low, the stains on the surface of the workpiece will be difficult to clean;

[0131] When the cleaning liquid for ultrasonic cleaning is adjusted to deionized water, it will make it difficult to clean the stains on the surface of the workpiece;

[0132] (6) Comprehensive analysis of Example 1 and Comparative Examples 1-2 shows that two consecutive sandblasting treatments will further improve the roughness and other properties of the sample to be tested;

[0133] When either the first sandblasting treatment or the second sandblasting treatment is omitted, the roughness of the sample will increase slightly;

[0134] (7) Comprehensive analysis of Example 1 and Comparative Example 3 shows that, compared with acid immersion, the corrosion effect of alkaline solution is poor, which leads to an increase in the roughness of the sample.

[0135] In summary, the surface treatment method provided by the present invention can efficiently and quickly process the selected laser melted titanium alloy samples, so that the surface roughness and dimensional deviation are within the required range, and the fluorescent penetrant test can be successfully passed in one time, reducing the cost caused by multiple fluorescent penetrant tests.

[0136] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A surface treatment method for a titanium alloy sample by selective laser melting, characterized in that: The surface treatment method comprises the following steps: The titanium alloy sample to be processed is subjected to a first sandblasting treatment, a polishing treatment, a second sandblasting treatment, an acid solution immersion treatment, an ultrasonic cleaning treatment and a purging treatment in sequence.

2. The surface treatment method according to claim 1, characterized in that: The thickness of the selected area laser melted titanium alloy sample is ≤1.2mm.

3. The surface treatment method according to claim 1 or 2, characterized in that: The pressure of the first sandblasting treatment is 0.5-0.55 MPa; Preferably, the single point residence time of the first sandblasting treatment is 10 to 15 seconds; Preferably, the blasting medium used in the first blasting process comprises black corundum; Preferably, the average particle size of the black corundum is 80-100 meshes.

4. The surface treatment method according to any one of claims 1 to 3, characterized in that: The polishing process includes polishing with a polishing head and ultrasonic polishing performed sequentially.

5. The surface treatment method according to claim 4, characterized in that: The polishing grinding head used for polishing comprises a resin polishing grinding head; Preferably, the precision of the resin polishing grinding head is 150-320 mesh; Preferably, the polishing time of the polishing grinding head is 6 to 15 minutes.

6. The surface treatment method according to claim 4, characterized in that: The polishing medium used in the ultrasonic polishing includes fiber oilstone; Preferably, the particle size of the fiber oilstone is 120-180#; Preferably, the ultrasonic polishing time is 3 to 8 minutes.

7. The surface treatment method according to any one of claims 1 to 6, characterized in that: The pressure of the second sandblasting treatment is 0.5-0.55 MPa; Preferably, the single-point residence time of the second sandblasting treatment is 7 to 12 seconds; Preferably, the blasting medium used in the second blasting process comprises black corundum; Preferably, the average particle size of the black corundum is 80-100 meshes.

8. The surface treatment method according to any one of claims 1 to 7, characterized in that: The mixed acid used for the acid leaching includes nitric acid, hydrofluoric acid and water; Preferably, the mass ratio of nitric acid, hydrofluoric acid and water is 3-4:1-2:5; Preferably, the concentration of the nitric acid is 65-68wt%; Preferably, the concentration of the hydrofluoric acid is ≥40wt%; Preferably, the acid solution immersion time is 3 to 15 minutes.

9. The surface treatment method according to any one of claims 1 to 8, characterized in that: The temperature of the ultrasonic cleaning is 40-50°C; Preferably, the ultrasonic cleaning time is 30 to 40 minutes; Preferably, the cleaning liquid used for the ultrasonic cleaning includes a hydrocarbon cleaning agent.

10. The surface treatment method according to any one of claims 1 to 9, characterized in that: The surface treatment method comprises the following steps: The titanium alloy sample to be processed with a thickness of ≤1.2 mm is sequentially subjected to the first sandblasting treatment, polishing treatment, the second sandblasting treatment, acid immersion, ultrasonic cleaning and purging treatment; The pressure of the first sandblasting treatment is 0.5-0.55 MPa, the single point residence time is 10-15 s, and the sandblasting medium used includes black corundum with an average particle size of 80-100 mesh; The polishing process includes polishing with a polishing head and ultrasonic polishing performed in sequence; the polishing time of the polishing head is 6 to 15 minutes, and the polishing head used includes a resin polishing head with a precision of 150 to 320 meshes; the ultrasonic polishing time is 3 to 8 minutes, and the polishing medium used includes a fiber oilstone with a particle size of 120 to 180#; The pressure of the second sandblasting treatment is 0.5-0.55 MPa, the single point residence time is 7-12 s, and the sandblasting medium used includes black corundum with an average particle size of 80-100 mesh; The acid leaching time is 3 to 15 minutes, and the mixed acid used includes nitric acid, hydrofluoric acid and water in a mass ratio of 3 to 4:1 to 2:5; the concentration of the nitric acid is 65 to 68 wt%, and the concentration of the hydrofluoric acid is ≥ 40 wt%; The temperature of the ultrasonic cleaning is 40-50° C., the time is 30-40 minutes, and the cleaning liquid used includes a hydrocarbon cleaning agent.